Comparative color stability assessment of orthodontic clear aligners: an in vitro study - Nancy Ajwa; Fatimah Radhi; Rana Aloraini; Ghadi AlSaydalani (Scientific Reports)
Abstract Objective To evaluate the stain resistance and color stability of four Clear aligners (CA) brands against various beverages at different intervals, along with assessing the elaboration of cleaning agents. Methods In a strictly controlled lab environment, 48 CAs from four different companies (Invisalign, EON, Clear Cap, and K clear) were immersed for seven days in six different beverages based on their pH (Pepsi, orange juice, milk, coffee, and black tea), as well as a control solution (distilled water). The VITA Easy-Shade compact colorimeter used the Commission International lightening L*a*b* color scheme to evaluate the color change of the aligners at four intervals. T0: before immersing in the solution; T1: twelve hours after immersion; T2: seven days after immersion; and T3/T4: fifteen minutes after exposure to two cleaning agents. The color values were then converted into National Bureau of Standards System (NBS) units. The statistical analysis was carried out using SPSS. A one-way ANOVA test was used to compare the mean color change values of all aligners and staining agents. Results A significant color change in aligners was observed after immersion in the stated solutions (p = 0.01). Additionally, there is a difference when washing with Invisalign foam and M3 cleaners (p < 0.001). Similarly, there were significant color variations between twelve hours and seven days after soaking (p = 0.01). Nonetheless, there were no significant differences in discoloration among the CAs’ manufacturing materials. Conclusions CAs’ staining ability at different time intervals after immersion in various solutions was clearly visible. Aligner cleanser use has a substantial influence on reducing acquired pigmentation. However, there were minimal differences in discoloration across CA brands.